An Ecological Multidisciplinary Approach to Protecting Society, Human Health, and the Environment at Nuclear Facilities. Issue 3 (13th June 2013) - Burger, Joanna; Gochfeld, Michael; Clarke, James; Powers, Charles W.; Kosson, David
Abstract As the United States and other countries move toward a greater reliance on nuclear energy, it becomes increasingly important to characterize the environment around such facilities to protect society, human health, and the environment. This article presents an ecological, multidisciplinary approach to gathering the information needed to establish baselines, site new nuclear facilities, protect existing nuclear facilities and nuclear wastes, improve the basis for emergency planning, devise suitable monitoring schemes to ensure continued protection, provide data to track local and regional response changes, and provide for mitigation, remediation, and decommissioning planning. We suggest that there are five categories of information or data needs: (1) geophysical, sources, fate and transport; (2) biological systems; (3) human health; (4) stakeholder and environmental justice; and (5) societal, economic, and political. All of these categories are influenced by temporal and spatial patterns, vulnerabilities, and global changes. These informational needs are more expansive than the traditional site characterization but encompass a suite of physical, biological, and societal needs to protect all aspects of human health and the environment, not just physical health. We suggest that technical teams be established for each of the major informational categories, with appropriate representation among teams and with a broad involvement of a range of governmental personnel, natural and social scientists, Native Americans, environmental justice communities, and other stakeholders. Although designed for nuclear facilities, the templates and information teams can be adapted for other hazardous facilities. © 2013 Wiley Periodicals, Inc.